2022
DOI: 10.1002/slct.202103273
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Optical Properties of Oxidized Poly Vinyl Alcohol

Abstract: Poly (viny1 alcohol) (PVA) was partially oxidized by alkaline KMnO 4 with an average carbonyl percentage of 65 %. PVA's photo physicochemical properties before and after the oxidation (OPVA) were investigated. The FTIR spectrum of OPVA revealed a new band at 1645 cm À 1 , corresponding to the carbonyl group and the XRD pattern reflecting an increase in the degree of crystallinity. Unlike pristine PVA, the UV-vis absorption spectra displayed the most attractive results through OPVA absorption in UV and visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The spectral profile of PVA is characterized by the presence of bands at 3398 cm −1 (OH stretching of PVA), 2928 cm −1 (CH asymmetrical stretching), 2864 cm −1 (CH 2 symmetrical stretching), 1653 cm −1 (CO stretching from the residual acetate group), 1462 cm −1 (CH scissoring) 1327 cm −1 (the deformation vibration of CH 2 ), 1101 cm −1 (COC stretching of the acetyl groups), and 843 cm −1 (CH rocking) 23 . The PVP profile showed two characteristic bands at 1680 cm −1 and 1283 cm −1 , corresponding to the stretching vibration of the CO groups and the stretching vibration of the CN groups in the PVP backbone, respectively 24 .…”
Section: Resultsmentioning
confidence: 99%
“…The spectral profile of PVA is characterized by the presence of bands at 3398 cm −1 (OH stretching of PVA), 2928 cm −1 (CH asymmetrical stretching), 2864 cm −1 (CH 2 symmetrical stretching), 1653 cm −1 (CO stretching from the residual acetate group), 1462 cm −1 (CH scissoring) 1327 cm −1 (the deformation vibration of CH 2 ), 1101 cm −1 (COC stretching of the acetyl groups), and 843 cm −1 (CH rocking) 23 . The PVP profile showed two characteristic bands at 1680 cm −1 and 1283 cm −1 , corresponding to the stretching vibration of the CO groups and the stretching vibration of the CN groups in the PVP backbone, respectively 24 .…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of PVA reveals a distinct peak at 2θ=21°, corresponding to the (101) plane, [27] indicating the semi‐crystalline nature of PVA. This semi‐crystallinity arises from the intermolecular hydrogen bonding among the PVA chains, resulting in a partial ordering of the polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…The literature extensively documents the preparation of oxidized polyvinyl alcohol through different processes that partially or completely introduce carbonyl functionalities by oxidizing hydroxyl groups. [21,27,28] Lu et al reported the solid-state oxidation of PVA using hydrogen peroxide and [19][20][21][22] copper(II). [29] Lin et al investigated the degradation of PVA in aqueous solutions under 365 nm UV light in the presence of persulfate, noting higher PVA oxidation in acidic solutions than alkaline solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are possible for PVA. The preparation of oxidized polyvinyl alcohol by adopting different processes, leading to partial or complete formation of carbonyl functionalities through the oxidation of hydroxyl groups, is well documented in the literature [21,27,28]. Lu et al have reported the solid-state oxidation of PVA using hydrogen peroxide and [19][20][21][22] copper (II) [29].…”
Section: Introductionmentioning
confidence: 99%